The relationship between selected blood lactate thresholds and match performance in elite soccer referees - Castagna, C.; Abt, G.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2002)
The aim of this study was to examine the relationship between selected blood lactate thresholds and competitive match activities in elite soccer referees. Eight elite-level referees (mean age, 37.6 +/- 3.4 years) were each observed during 2 Serie A matches (n = 16), and the mean of each match activity was used for analysis. Match activities were monitored using a technology similar to that reported by Ohashi and others. Blood lactate thresholds were assessed under field conditions during a progressive multistage protocol. Running velocities attained at selected blood lactate concentrations (2 and 4 mmol x L(-1), V2 and V4, respectively) were chosen because these are commonly used to assess endurance performance. Analyses of correlations were performed considering V2 and V4 values as independent variables and total distance, maximal velocity distance (runs performed at velocities faster than 24 km x h(-1)) and high-intensity activity distance (runs performed at velocities faster than 18 km x h(-1)) as dependent variables. Significance was set at p </= 0.05 for all measurements. The V2 and V4 values were 10.9 +/- 1.8 km x h(-1) and 13.6 +/- 1.4 km x h(-1) (10.5-15.0), respectively. Mean peak-lactate corresponded to 9.4 +/- 1.6 mmol x L(-1). The V4 value correlated moderately with the total distance covered during the match (r = 0.73, p < 0.05). The results demonstrate the positive relationship of the running velocity attained at a blood lactate concentration of 4 mmol x L(-1) to the total amount of distance covered by a referee during a match.